2020
DOI: 10.1016/j.semarthrit.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in rheumatic disease patients on immunosuppressive agents

Abstract: To analyze clinical characteristics and outcome of COVID-19 patients with underlying rheumatic diseases (RD) on immunosuppressive agents. Method: A case series of COVID-19 patients with RD on disease modifying anti-rheumatic drugs (DMARDs) were studied by a retrospective chart review. A literature search identified 9 similar studies of single cases and case series, which were also included. Results: There were 4 COVID-19 inpatients with RD from our hospital, and the mean age was 57 § 21 years. Two patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 41 publications
4
64
1
2
Order By: Relevance
“…Their use is associated with IgM deficiency in a substantial number of patients, while their impact on IgG and IgA levels is more limited (Kridin and Ahmed, 2020). In line with our data, recent studies reported that anti-CD20 therapy could be associated with a higher susceptibility to contract SARS-CoV-2 and develop severe COVID-19 (Guilpain et al, 2020;Hughes et al, 2020;Safavi et al, 2020;Schulze-Koops et al, 2020;Sharmeen et al, 2020;Sormani et al, 2020). Whether this is associated to the preferential depletion of IgM-producing B cells by these treatments (Looney et al, 2008) remains to be shown.…”
Section: Discussionsupporting
confidence: 78%
“…Their use is associated with IgM deficiency in a substantial number of patients, while their impact on IgG and IgA levels is more limited (Kridin and Ahmed, 2020). In line with our data, recent studies reported that anti-CD20 therapy could be associated with a higher susceptibility to contract SARS-CoV-2 and develop severe COVID-19 (Guilpain et al, 2020;Hughes et al, 2020;Safavi et al, 2020;Schulze-Koops et al, 2020;Sharmeen et al, 2020;Sormani et al, 2020). Whether this is associated to the preferential depletion of IgM-producing B cells by these treatments (Looney et al, 2008) remains to be shown.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, those patients treated with Rituximab [137], or Secukinumab appeared to have worst outcome defined by a higher rate of ICU admissions [138]. Those patients treated with Rituximab and Secukinumab exhibited high concentrations of IL-6, suggesting that these medications failed to modulate IL-6 which has been strongly associated with mortality in COVID-19 [138]. In addition, CD20 blockers could impair B cells function hindering the production of NAbs against SARS-CoV-2 [138].…”
Section: Cytokine Storm Syndrome (Css)mentioning
confidence: 99%
“…The pandemic condition caused Malaysia to lockdown various educational institutions, tourism, and others, so that it could indirectly have an impact on reducing air pollution by offset by local meteorological factors and anthropogenic emissions (60). In addition, in the YRD Region there was also a decrease in air pollution in SO 2 , NOx, PM 2,5 pollutants and Volatile Organic Compounds (VOCs) due to activity restrictions during the Covid19 pandemic (53).…”
Section: Discussionmentioning
confidence: 99%